Wearable EEG Device for Continuous Spike–Wave in Sleep - Oguni, Hirokazu (Pediatr Neurol Briefs, 2020)
Investigators from the Hospital Dona Estefânia, Escola Superior de Tecnologias e Saúde de Lisboa and Centro Hospitalar Psiquiátrico de Lisboa investigated 38 patients with continuous spike-wave of sleep (CSWS) syndrome.